2011
DOI: 10.1007/s11676-011-0198-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of natural regeneration status and diversity of tree species in the biodiversity conservation areas of Northeastern Bangladesh

Abstract: A study was conducted at two-biodiversity conservation areas of Northeastern Bangladesh (a part of Sylhet Forest Division) to assess the species composition, diversity and density of natural regeneration of tree species both indigenous and exotic species. Data were collected by stratified random quadrate method during Totally 200 circular plots of 2 m×2 m in size had 5 different habitat types of plants namely; forest, roadside, homestead (surrounding forest dwellers house), fallow land and others (canals, stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 16 publications
5
74
1
4
Order By: Relevance
“…The change in microclimate also affects the seedlings, saplings and young trees, etc. which are crucial for regeneration of forest (Rahman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The change in microclimate also affects the seedlings, saplings and young trees, etc. which are crucial for regeneration of forest (Rahman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a part of a Wildlife Sanctuary its floral composition, structure and diversity is needed to be known for managerial decision making and development planning. In Bangladesh many researcher investigated plant species diversity and forest stand structure (Hossain et al 1997;Rahman and Hossain 2003;Alamgir and Al-Amin 2005;Motaleb and Hossain 2011;Rahman et al 2011;Hossain et al 2012;Hossain et al 2013). But, Kamalachari forest lacks information regarding structural composition, stocking and conservation issues of Kamalachari natural forests.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated value of evenness index that are almost similar for each category and index of dominance of the study areas revealed that the total number of individuals are more evenly distributed among all species present at the two study sites. Rahman et al [91], Rahman et al [92], and Top et al [93] believed that the higher the value of diversity, the greater the stability of community will be.…”
Section: Consensus On Managing Ailments Among Informantsmentioning
confidence: 99%